The discourse of digital persuasion: unmasking Aristotelian rhetorical strategies in Harvard's EdX MOOCs - Ricahyono, Sigit (Universitas PGRI Madiun, 2023)
This study looked into how Harvard University's EdX Massive Open Online Courses (MOOCs) strategically employed the Aristotelian rhetorical aspects of pathos, ethos, and logos to comprehend their digital persuasion methods. It employed content analysis to examine three MOOCs'